Prymas Józef Glemp wobec opozycji politycznejw latach 1983–1984 - Rafał Łatka (Warszawskie Studia Teologiczne)
Card. Józef Glemp's attitude towards political opposition was critical and sceptical throughout the entire decade of the 1980s. The above mentioned analysis sheds some light on the attitude of the primate to the underground in years 1983- 1984. The author presents the primate's approach to this problem in the period of preparations for the second pilgrimage of John Paul II to the Homeland and the tightening of religious policy by the authorities of the Polish People's Republic, which took place as a result of the evaluation of the effects of the papal visit. It should be emphasised that the detachment from the activity of the opposition also resulted in the primate's critical approach to cooperation of the clergy with the political underground. This article discusses it on the example of the attitude of card. Glemp to priest Popiełuszko. However, the detachment and scepticism towards the opposition did not mean that the primate and the Polish Episcopate did not stand up for the repressed by the authorities. They did it regularly and the chairman of the Polish Episcopal Conference addressed this issue, among others, during the talks with W. Jaruzelski.